Penampilan Produksi Kelinci Fase Pertumbuhan Menggunakan Wafer Ransum Komplit Berbahan Tepung Inti Biji Karet - Harahap, Anwar Efendi Harahap; Rasmi, Ade Septika; Hidayati, Hidayati (Jurnal Sains Peternakan, 2020)
Rubber seed is agricultural waste can used for alternatif feed. Rubber seed use not enough for make ends meet rabbit, additional feed is needed to complete it to mix the ingredient needed technology, technology that can be used, one of which is wafers. This study aims to determine the performance of the growth phase of rabbit production by using a complete wafer ration with the addition of 0%, 3%, 6% and 9% rubber seed core flour. Observations made in this study were body weight gain, ration consumtion, ration conversion, and feed costs. This study using completely randomized design (CRD), which consists of 4 treatments and 3 replications. Addition of rubber seed flour in ingredients not significantly up to the level of 9% the production performance of male local rabbits in the growth phase seen from ration consumtion, body weight gain, ration consumtion, and ration conversion. High feed cost is found in the addition of 3% of rubber seed core flour and the lowest feed cost is found in the addition of 9% of rubber seed core flour.